Effect of aluminium doping on structural, optical, photocatalytic and antibacterial activity on nickel ferrite nanoparticles by sol–gel auto-combustion method - Naik, M. Madhukara; Naik, H. S. Bhojya; Nagaraju, G.; Vinuth, M.; Vinu, K.; Rashmi, S. K. (Journal of materials science. Materials in electronics, 2018)
The present work designates the preparation of nanocrystalline nickel ferrite and aluminium-doped nickel ferrite nanoparticles with general formula NiAl x Fe 2−x O 4 (x = 0–0.7) prepared by the sol–gel auto-combustion method. The structural (XRD and FTIR), morphological (SEM with EDAX, HRTEM with SAED) and optical (UV–Visible DRS and Luminescence spectroscopy) properties of the products were characterized. XRD studies revealed the formation of the single phase with a cubic spinel structure with an average crystallite size varies between 19 and 38 nm. The increase in aluminium content caused the variation in the lattice parameter (8.2782–8.3366 Å). SEM images shows the morphology have nanocrystalline behavior with a spherical structure. FTIR represents the characteristic peaks of M–O vibrations in tetrahedral (~ 591 cm −1 ) and octahedral (~ 398 cm −1 ) sites. From the UV–Vis DRS spectra, the band gap is decreasing with increasing doping, estimated to be 2.03–1.90 eV. The luminescence spectrum displays violet, blue, green, and orange emission. The aluminium-doped nickel ferrite nanoparticles act as an exceptional photocatalyst for the degradation of rose bengal dye (99.8% in 150 min) with respect to bulk material (63% in 150 min) under visible light (300 W tungsten lamp) irradiation. Furthermore, these nanoparticles were acted against gram-negative bacteria stain ( Salmonella typhi, Pseudomonas aeruginosa , and Escherichia coli ).